2005
DOI: 10.1021/ma051081s
|View full text |Cite
|
Sign up to set email alerts
|

ATR-FTIR Spectroscopic Study on Hydrogen Bonding of Poly(N-isopropylacrylamide-co-sodium acrylate) Gel

Abstract: Diameter decrement by the repeated exchange of solvent water has been reported in a polyelectrolyte hydrogel ionized by sodium acrylate in its swollen state. This behavior has been attributed to the exchange of counterions of carboxyl groups and the formation of hydrogen bonding. In this paper, the formation and destruction of hydrogen bonding in poly(N-isopropylacrylamide-co-sodium acrylate) (NIPA/SA) gel were studied using Fourier transform infrared (FTIR) spectroscopy with attenuated total reflection (ATR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 24 publications
4
55
0
Order By: Relevance
“…Figure 6a shows the ATR FTIR spectra of the PSAAl(x) gel (x 5 1, 2, 3, and 4). As is shown in this figure, the overall features of the spectra were same and two strong absorption peaks were observed at around 1550 and 1410 cm 21 , which did not strongly depend on x. These peaks were assigned to the C¼ ¼O stretching vibration of the ionized carboxyl group (À ÀCOO 2 ).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Figure 6a shows the ATR FTIR spectra of the PSAAl(x) gel (x 5 1, 2, 3, and 4). As is shown in this figure, the overall features of the spectra were same and two strong absorption peaks were observed at around 1550 and 1410 cm 21 , which did not strongly depend on x. These peaks were assigned to the C¼ ¼O stretching vibration of the ionized carboxyl group (À ÀCOO 2 ).…”
Section: Resultsmentioning
confidence: 52%
“…These peaks were assigned to the C¼ ¼O stretching vibration of the ionized carboxyl group (À ÀCOO 2 ). On the other hand, the broad absorption peaks at 1750-1650 cm 21 and 1380-1150 cm 21 , which seemed to consist of multiple components, decreased monotonically with increasing x. This evidence indicated that the degree of crosslinking might affect the intermolecular force between the carboxyl groups and Al ions in a monotonic fashion with increasing x.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…11 As the e-PL content in the e-PL/PAA complexes increased, the C¼O stretching intensities of the dimer and the free forms decreased, and the intensity of the peak at 1402 cm À1 increased. Because the COO À stretching vibration was observed in the 1400 cm À1 region, 12 there was a third form of carboxyl groups that we refer to as the ionized form. IR measurements showed that three forms of carboxyl groups exist in the e-PL/PAA complex, namely (1) the ionized form, (2) the dimeric form and (3) the free form.…”
Section: Ir and Dsc Measurementsmentioning
confidence: 99%
“…Recently, Suzuki and coworkers reported that poly(sodium acrylate) (PSA) and poly(N-isopropylacrylamide-co-sodium acrylate) (NIPA-SA) gels deswelled under repeated exchange of external water, which was attributed to protonation of the carboxyl groups and the resultant formation of inter-and/or intramolecular HBs between -COOHs. Further interestingly, the gels showed a discontinuous reswelling at a certain elevated temperature because of the destruction of HBs [7,8]. However, the thermo-swelling was not reversible; namely, with decreasing the temperature the gel kept the swollen state.…”
Section: Introductionmentioning
confidence: 97%